Théorie des contextes et relations internationales : Départ de la première guerre d’Indochine - Vuong, Thanh (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1986)
Bateson's "Eurêka" has been his application of Russell and Whitehead's theory of types to the social sciences. They had postulated a discontinuity between the levels of the members of a class and a class of classes and so on. Hence a class may not be a member of itself. The cat scratches and the word "cat" does not bite. Confusion between levels, or the signifier and the signified, or the map and the territory, or the menu and the meal, is a sign of disorder. Having been introduced to Bateson's ecology, Anthony Wilden has formulated a theory of contexts, already present in "System and Structure". In order to avoid simplicity through the flattening of social and organic levels into inorganic levels of matter-energy, the theory of contexts suggest the organisation of constraints, complexites, or levels of reality into levels of logical types, using the rule of extinction. It goes on to suggest the use of the rule of commutation to eliminate spurious similarities and inappropriate symmetries which lead to oppositions and Imaginary "contradictions". It is suggested to use Korzybski and Hayakawa's rule of communication in order to get over conflicts due to misperception. To illustrate all of this, we propose to dismanthe the processes which have led to the misunderstanding behind the first Indochinese war of 1946-1954. From one misunderstanding to another, the VPA (Vietnam People's Army), in the 1980's, mobilised at the Kmer-Siamese border, at the door of Thailand who since 1939 has claimed to be the land of the Thais and heir to the Champa empire which was established in 192 and, soon after 1471, was dissolved by the "gnawing" of the Vietnamese peasants in their "long march" towards the South. The most revolting of working, conjugal and international disputes is that which emerge from misperceptions where each party is convinced of its own good will and of the foul bad will of the other. A mutual consent regarding the context, that of metacommunication, may lead to a common signification (consensus) of beings, events and objects.